STUDI POPULASI IKAN BETUTU (Oxyeleotris marmorata, Blkr.) DALAM UPAYA PENGENDALIAN DI WADUK PANGLIMA BESAR SOEDIRMAN, BANJARNEGARA - Adhitya Moersid (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
As one of the introduction species, Betutu Fish has an important role to the controlling effort at P.B Soedirman Reservoir. Generally, the population index of the indigenous fresh water species has decreased. It is caused by the existence of the introduction fish that threat the indigenous fish species, so the population becomes homogeneous. This research is aiming to find out about two things, which is: a) the abundance, sex ratio, size dispersion, weight and length of the Betutu Fish in P.B Soedirman Reservoir; and also b) the influence of environmental factors on the abundance of Betutu Fish in P.B. Soedirman Reservoir, Banjarnegara. This research is using the survey method with purposive random sampling, in 9 location which has been done twice on June and July 2013. The population of parameter has been analyze by quantative method, while the correlation of water quality against to the abundance used the Spearman Rank correlation analysis method. The research result showed that the density was 57 fishes/307,5 m2; the sex ratio was 1:0,08 with 91,3% male and 8,7% female percentage; the size dispersion was even in every sample areas; and the value of b is obtained for the weight and length connection, which is close to isometric value (b=3). For the whole water quality aspect, whether physic or chemistry that has been measured during the research in the reservoir was still in normal range. It is supported by the Spearman Rank analysis that concerns about the correlation of physic and water chemistry to the density; and it turned out to be that both of the element have correlation even though not too significant. Keywords: Betutu fish, population, reservoir,  abundance, water quality.